Determinación del efecto de la temperatura en la curva de viscosidad en crudos pesados y extrapesados de Colombia- Venezuela (2022)
The high viscosity of heavy and extra-heavy crudes (due to their low mobility) tends to hinder extraction and increase the cost of production processes in these reservoirs, due to the need to implement both chemical or heat injection to allow the ease of movement of these crudes from the reservoir to surface production facilities. When speaking particularly of Thermal Enhanced Recovery (EOR-Thermal) processes, it is important to understand how the temperature generation in these processes translates into a vital expense to determine the viability or application of these mechanisms in the production of viscous crudes. That is why studying the closed behavioral relationship between an increase in temperature versus viscosity can be the starting point to understand which viscosity decrease in the crude could generate the greatest production benefits with the lowest caloric or energy rate implemented in the EOR-Thermal process.